Analisis Yuridis Penegakan Hukum Lingkungan Terhadap Pencemaran Sungai Citarum - Rihan Rizky; M Z Syafiq Haidar Hisyam; Muhammad Rafa; Fathir Putra Maulud; Ahmad Ramdani (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes the enforcement of environmental law in addressing pollution in the Citarum River by employing a normative legal research method with statutory and conceptual approaches. The analysis focuses on the regulatory framework, the implementation of law enforcement mechanisms, and the challenges affecting their effectiveness in practice. The Citarum River plays a strategic role in supporting social, economic, and ecological systems; however, it faces serious pressures from industrial pollution, domestic waste, and spatial planning issues. The national legal framework provides a basis for environmental protection through the regulation of water quality standards, environmental permitting regimes, and the imposition of administrative and criminal sanctions. The implementation of environmental law enforcement reflects ongoing efforts in monitoring and sanctioning polluters, particularly corporate actors, although overall legal compliance remains suboptimal. The effectiveness of enforcement is influenced by institutional constraints, technical challenges in evidentiary processes, inter-agency coordination issues, and social factors within affected communities. This study emphasizes the importance of strengthening institutional coordination, enhancing the capacity of law enforcement authorities, and integrating environmental restoration approaches. Consistent and equitable enforcement of environmental law is expected to contribute to improvements in environmental quality, ensure the long-term sustainability of the Citarum River, and support the protection of the public’s right to a healthy and sustainable environment in Indonesia.